Government support, internal perceptions, and mountain farmers’ conservation tillage adoption: evidence from Enshi City, Hubei Province - Ma, Yan; Sun, Zhen (Frontiers in Environmental Science, 2025)
As a vital measure for promoting the green transformation of agriculture, the analysis of the impact of government support and farmers’ internal perceptions (subjective norms, attitudes toward behaviour, behavioural intention) on the adoption of conservation tillage technology is essential for optimizing policy design and promoting sustainable agricultural development. Based on the Stimulus-Organism-Response (SOR) theoretical model, this study constructs a relational model involving government support, farmers’ internal perceptions, and conservation tillage technology adoption behaviour. Most existing studies have examined internal or external factors in isolation, thus lacking an understanding of how government support influences farmers’ adoption of conservation tillage through psycho-institutional interactions. This study addressed this gap by using the integrated SOR framework and Structural Equation Model. An empirical analysis was conducted using survey data from 245 farmers in Enshi City, Hubei Province. The effective questionnaire rate was 94.23%. The results show that both government support and farmers’ internal perceptions significantly positively influence conservation tillage technology adoption behaviour. Furthermore, bootstrap analysis with 2000 replicates demonstrated that internal perceptions serve both as individual and chain mediators between government support and conservation tillage technology adoption behaviour. Therefore, in promoting conservation tillage technology, the role of government support should be effectively utilized. By strengthening farmers’ internal perceptions, their awareness, familiarity, and satisfaction with conservation tillage technology can be increased, thus encouraging its adoption and dissemination. This will contribute to implementing the rural revitalization strategy and achieving the green transformation of agriculture.